A SOME ISSUES IN THE ANTONYMY OF PHRASEOLOGICAL UNITS IN THE ENGLISH LANGUAGE (Scientific journal of the Fergana State University, 2025)
This article seeks to define the scope of phraseology as an autonomous branch of linguistics distinct from its individual constituents. The article deals with the topic of phraseological antonymy, namely root and affixal antonymy. Five contexts of modern English that constitute opposition are examined in order to find systematic regularities of contrast. It also analyzes phraseological units with antonyms where two types of oppositions are distinguished: one where the opposition is internal within the unit and the other where the opposition is external and only appears in certain phrases. The methodological basis is the study of phraseological antonyms from the point of view of translation, which analyzes the relations of various types of lexical integration and substitution of constituents in antonymous units. The results clarify that the phraseological units that are regularly used in contexts with antonymy concentration are the ones that need extra focus.